Full loss analysis for a multicrystalline silicon wafer solar cell PV module at short-circuit conditions - Peters, Marius; Guo, Siyu; Liu, Zhe (Progress in Photovoltaics, 2016)
We present an extended analysis to quantify losses in a module under short-circuit conditions. The presented method includes an analysis of the area-related losses in a full-sized module and introduces the concept of "effective area coverage." The effective area coverage accounts for the amount of light lost on a certain type of area and is different from the actual area coverage, if light trapping area occurs. An example for this effect is light reflected from the backsheet, trapped in the glass cover and reaching the solar cell. Based on our analysis, the effective solar cell area is increased by 5% absolute by this effect. Furthermore, we used an extension of Basore's model for modules in the loss analysis and used it to quantify losses in one exemplary, encapsulated multicrystalline silicon wafer solar cell. These losses are absorption in the rear reflector (corresponding to a loss of 3.5 mA/cm2 on the active solar cell area), collection losses (3.4 mA/cm2) and free carrier absorption (0.18 mA/cm2). Finally, the presented analysis allowed us to calculate a breakdown of all losses in a full-sized module under short-circuit conditions. A list of all considered losses sorted by the corresponding current is presented at the end.
CRIS-Team Scopus Importer:2023-03-07
Keywords: loss analysis; multicrystalline silicon wafer solar cells; PV modules